2012
DOI: 10.1002/app.38122
|View full text |Cite
|
Sign up to set email alerts
|

Ketimine substituted polyphenol: Synthesis, characterization and investigation of its thermal and electrochemical properties

Abstract: Oxidative polycondensation of 3‐(1‐(2‐phenylhydrazono)ethyl)phenol (3‐PHEP) was studied using oxidants such as sodium hypochlorite, air (O2) and hydrogen peroxide in an aqueous alkaline medium under various polymerization conditions. The polymerization yield, molecular weight, solubility, and thermostability of the polymer were investigated. The macromolecular structure of the resulting polymer was characterized by elemental analysis, ultraviolet–visible, Fourier transform infrared, and nuclear magnetic resona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Previously, we focused on the formation of NNO-type poly(phenoxy-ketimine). 12 On the basis of these studies, we decided to proceed to the construction of NNO-type poly(phenoxy-imine).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we focused on the formation of NNO-type poly(phenoxy-ketimine). 12 On the basis of these studies, we decided to proceed to the construction of NNO-type poly(phenoxy-imine).…”
Section: Introductionmentioning
confidence: 99%
“…According to the gel permeation chromatography (GPC) measurements, poly (4-PHMP) and poly(3-PHEP) have high molecular weight that values change 6,500 to 17,717 depending on the polymers structures [9,10]. The structural analyses show that the prepared polymers consist of C-C and C-O-C coupling systems ( Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…In this connection, conductive polymers with higher level of conductivity without doping are of interest. In this work, we discuss semiconductive properties of the polymers obtained by oxidative coupling polymerization of 3-(1-(2-phenylhydrazono) ethyl)phenol (3-PHEP) [9] and 4-((2-phenylhydrazono)methyl) phenol (4-PHMP) [10] by formation of the phenylhydrazono (C 6 H 5 -NH-N=C(R)-) type structures with π-conjugation with participation of the nitrogen atoms in polymer pendent groups.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks observed at 3150 and 3272 cm À1 are due to the phenolic eOH groups of 4-MMAP and P(4-MMAP), respectively. While the sharp peak observed at 1621 cm À1 in the spectrum of the monomer belongs to the characteristic eCH]Ne vibration, and the same peak is seen as a shoulder at 1624 cm À1 in the spectrum of the polymer [8,14,20]. The presence of the characteristic eCH]Ne peak of the Schiff base in the FTIR spectrum of P(4-MMAP) indicates that the azomethine groups are preserved in the polymeric structure [20].…”
Section: Ftir Spectramentioning
confidence: 98%
“…Oxidative polycondensation reactions carried out using NaOCl, H 2 O 2 and O 2 oxidants are one of the most widely used method for the chemical polymerization. The advantages of this approach are the cheapness of the oxidants, high solubility of the synthesized polymer, mild reaction conditions and occurrence of environmentally friendly byproducts, such as NaCl and H 2 O [13,14]. A number of studies have been reported on the synthesis of this class of polymers using these oxidants up to the present by .…”
Section: Introductionmentioning
confidence: 97%